Patient Progress Following Nutritional Care For Superficial Dermal To Full Thickness Burns - Dita Noviyanti; Ibnu Zaki; Widya Ayu Kurnia Putri (Jurnal Gizi dan Kesehatan Keluarga, 2024)
Background: Burns are a type of injury that require serious medical attention. The increased nutritional needs are a major issue in burn cases, where fulfilling these needs is crucial to support the tissue repair process and address the metabolic consequences of the injury. The nutritional care process is a critical thinking approach that focuses on handling individual cases specifically. This article aims to assess the progression of patients following nutrition care process in cases of Superficial Dermal to Full Thickness Burns. Method: This study employed a case study design. Nutrition care process was provided to a 39-year-old male patient who sustained burns on his chest, hands, genital area, and legs after being scalded by hot water while working in a factory. The medical diagnosis was superficial dermal to full thickness burn covering 49% TBSA caused by hot water and chemicals. Nutrition care process was provided for a duration of five days. Data collection was conducted through observation, in-depth interviews, and medical record analysis, including physical and clinical examinations as well as laboratory parameters. Results: The nutrition care process for the patient with Superficial Dermal to Full Thickness Burns began with screening, assessment, diagnosis, intervention, monitoring, and evaluation. A high-energy, high-protein diet was administered for five days in the form of regular meals. There was an improvement in physical and clinical indicators, as well as dietary intake, following five days of nutritional care.